Safe Scholarship - Rehman, Dr. Saeed Ur (Journal of Research in Humanities, 2023)
This article attempts to construct a theoretical category that can be applied to knowledge production within the fields of culture and identity politics. To extrapolate the category, safe scholarship, the work of Akbar S. Ahmed and its intellectual ramifications are examined and unpacked. Identity, religion, and culture are not fixed concepts but regulatory regimes and safe, uncritical intellectuals seek to keep the fluid constructs in a state of (imagined) fixity. Safe scholarship helps perpetuate the epistemic as well as political status quo. The article builds the argument that production of critique, in contrast to safe scholarship, opens up social and public spaces for those subjects and social conditions usually relegated to the margins. The hypothesis that emancipatory potential of critique is greater than safe scholarship is examined in relation to the work of Akbar S. Ahmed.